Earomyia impossibile Morge, 1959: Derivatio nominis (Diptera: Lonchaeidae). - Morge, Günter (Contributions to Entomology = Beiträge zur Entomologie, 1983)
The derivation of the name of the species impossibile of the genus Earomyia is explained and confirmed, and it is stated that impossibile as part of the binominal term with Earomyia is not the neuter form of the Latin adjektive imposibilis, but the italian word impossibile.